THE ROLE OF METADISCOURSE IN ONLINE MENTAL HEALTH NEWS: A CORPUS-ASSISTED DISCOURSE ANALYSIS - Benard Mudogo; Stella Wangari Muriungi (Journal of Community Mental Health and Public Policy, 2026)
Background: The online dissemination of news articles about sensitive subjects, such as mental health, influences the perception of individuals with mental illness, service providers, and policies that shape their lives. Purpose: This study investigates interactional metadiscourse in online news reporting on mental health issues, focusing on how lexical choices shape readers' attitudes. Method: Using Hyland and Jiang's (2016, 2021) interpersonal model of communication, which emphasizes disciplinary variation and writer–reader interaction in written discourse, we adopted an explanatory sequential mixed-methods design to analyze a corpus of 45 online news articles on mental health published between 2022 and 2024 in five mainstream Kenyan media outlets. The analysis identifies five categories of interactional metadiscourse markers: hedges, boosters, attitude markers, self-mentions, and engagement markers. Results: Metadiscourse markers are not employed neutrally but frequently establish negative portrayals of individuals with mental illness. While interactional metadiscourse enhances textual cohesion and reader engagement, caution is needed to avoid reinforcing stigma and misinformation. Conclusion: The study highlights the need for careful language usage in news reporting on mental health to foster accurate public understanding and facilitate constructive policy discourse. Abstrak Latar Belakang: Penyebaran berita artikel daring tentang subjek sensitif, seperti kesehatan mental, memengaruhi persepsi individu dengan penyakit mental, penyedia layanan, dan kebijakan yang membentuk kehidupan mereka. Tujuan: Studi ini menyelidiki metadiskursus interaksional dalam pemberitaan daring tentang isu kesehatan mental, dengan fokus pada bagaimana pilihan leksikal membentuk sikap pembaca. Metode: Menggunakan model komunikasi interpersonal Hyland dan Jiang (2016, 2021), yang menekankan variasi disiplin dan interaksi penulis-pembaca dalam wacana tertulis, kami mengadopsi desain metode campuran sekuensial eksploratif untuk menganalisis korpus 45 artikel berita daring tentang kesehatan mental yang diterbitkan antara tahun 2022 dan 2024 di lima media arus utama Kenya. Analisis mengidentifikasi lima kategori penanda metadiskursus interaksional: penegasan, penguatan, penanda sikap, penyebutan diri, dan penanda keterlibatan. Hasil: Penanda metadiskursus tidak digunakan secara netral tetapi sering kali membentuk penggambaran negatif tentang individu dengan penyakit mental. Meskipun metadiskursus interaksional meningkatkan kohesi tekstual dan keterlibatan pembaca, kehati-hatian diperlukan untuk menghindari penguatan stigma dan informasi yang salah. Kesimpulan: Studi ini menyoroti perlunya penggunaan bahasa yang cermat dalam pemberitaan tentang kesehatan mental untuk mendorong pemahaman publik yang akurat dan memfasilitasi wacana kebijakan yang konstruktif.